Endoscopic Ultrasound-Guided Pancreatic Duct Drainage: Techniques and Literature Review of Transmural Stenting - Akira Imoto; Takeshi Ogura; Kazuhide Higuchi (Clinical Endoscopy, 2020)
Endoscopic ultrasound-guided pancreatic duct drainage (EUS-PD) has emerged as an option in patients with failure of retrograde access to the pancreatic duct (PD) because of difficulty in cannulation or surgically altered anatomy. This article provides a comprehensive review of the techniques and outcomes of EUS-PD, especially EUS-guided pancreatic transmural stenting. The clinical data derived from a total of 401 patients were reviewed in which the overall technical and clinical success rates were 339/401 (85%, range 63%–100%) and 328/372 (88%, range 76%–100%), respectively. Short-term adverse events occurred in 25% (102/401) of the cases, which included abdominal pain (n=45), acute pancreatitis (n=17), bleeding (n=10), and issues associated with pancreatic juice leakage such as perigastric or peripancreatic fluid collection (n=9). In conclusion, although EUS-PD remains a challenging procedure with a high risk of adverse events such as pancreatic juice leakage, perforation, and severe acute pancreatitis, the procedure seems to be a promising alternative for PD drainage in patients with altered anatomy or unsuccessful endoscopic retrograde pancreatography.